Development of metacomputer network agent-based applications - Volchikhin, V.I.; Karamysheva, N.S.; Gorynina, A.V.; Zinkin, S.A. (Известия высших учебных заведений. Поволжский регион:Технические науки, 2022)
Background. Despite the fact that by now new scalable architectures have been developed for distributed computing systems containing hundreds and thousands of computers, the task of creating transparent software of the “middleware” level remains urgent. The technology retrospective chain includes cloud, grid and metacomputer technologies, as well as various utility computing options. The creation of Internet-scale metacomputer technologies, tested at the completion of a number of well-known research projects, is of particular interest. The organization of effective management of the huge amount of resources that are available in a network environment deployed over a large area is a large and difficult problem in the implementation of distributed computing. The object of the study is metacomputer systems implemented on the basis of global networks, and the subject of the study is the organization of control of global computational processes in networks based on metacomputer technology. The purpose of the study is an improvement of this technology, which will allow considering a network with a given communication infrastructure as a single resource with the possible organization of arbitrary distributed algorithms. Materials and methods. The studies are carried out on the basis of the construction and software implementation of a conceptual model of distributed computing, implemented in a virtual metacomputer environment, which is the result of the integration of network, grid and cloud systems with agent-based systems. Results. The organization of metacomputer- based agent-based network distributed computing, which implements the basic constructions of distributed programming, where the network is really considered as a computer with distributed program control (message-driven computing), but not as a means of implementing the simplest client-server or master-slave applications. Modules, or agents, of a distributed application are capable of operating both in a reactive mode, waiting for data to be received and control transfer, and in a proactive mode, requesting data and control from previous modules (agents). Conclusions. Experiments carried out on a real network made it possible to confirm the operability of a metacomputer application and its ability to scale and expand its functional capabilities up to the properties of cloud-based network technologies AaaS (Agent as a Service) and FaaS (Function as a Service).